Desain Profil C+ Struktur Baja Ringan Pada Konstruksi Rangka Atap - Okazar, Okazar; Badri, Muftil; Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Light gauge steel is the latest innovation in overcoming material problems in the use of roof construction,especially the roof of the house. Generally, the construction of the roof of the house was made of wood, butbecause of the scarcity of wood made there should be a diversion in the use of materials. The use of light gaugesteel as a roof construction of the house has not been fully accepted by all of societies in general, due toconcerns in its strength. So this thesis discusses about the strength of the material and search for a better profilewithout any reduction of the existing structural material in the market. The profile design is the development ofan existing profile design or commercial profile. Testing of the comparison of new profile design results withcommercial profiles is done by simulation of Autodesk Inventor 2010. Simulation results are in the form ofcomparison of numbers. The result of the design number are better when compared from the commercialprofile then the design was chosen with through considerations.Keywords: Light Gauge Steel, Autodesk Inventor 2010